1996
DOI: 10.1177/00957984960222002
|View full text |Cite
|
Sign up to set email alerts
|

The Schedule of Racist Events: A Measure of Racial Discrimination and a Study of Its Negative Physical and Mental Health Consequences

Abstract: In this article, the authors develop a brief questionnaire that assesses racist discrimination in the lives ofAfricanAmericans, and conduct preliminary studies with it. The Schedule of Racist Events (SRE) is an 18-item self-report inventory that assesses the frequency of racist discrimination (specific, stressful racist events) in the past year (recent racist events) and in one's entire life (lifetime racist events), and measures the extent to which this discrimination was evaluated (appraised) as stressful (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,036
10
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 978 publications
(1,094 citation statements)
references
References 14 publications
47
1,036
10
1
Order By: Relevance
“…However, a key strength of this item is that it measured both positive and negative discrimination, whereas existing multi-item validated measures of perceived discrimination focus only on negative discrimination. [13][14][15] In conclusion, we found that there is no statistically significant independent relationship between negative discrimination and the utilization of standard preventive health services, nor is there an independent relationship between positive discrimination and utilization of most services. Future studies exploring the link between perceived discrimination and health outcomes should focus on biological mechanisms 2 or other health behaviors that may be shaped by perceived discrimination, such as following medical advice or treatment adherence.…”
Section: Discussionmentioning
confidence: 50%
“…However, a key strength of this item is that it measured both positive and negative discrimination, whereas existing multi-item validated measures of perceived discrimination focus only on negative discrimination. [13][14][15] In conclusion, we found that there is no statistically significant independent relationship between negative discrimination and the utilization of standard preventive health services, nor is there an independent relationship between positive discrimination and utilization of most services. Future studies exploring the link between perceived discrimination and health outcomes should focus on biological mechanisms 2 or other health behaviors that may be shaped by perceived discrimination, such as following medical advice or treatment adherence.…”
Section: Discussionmentioning
confidence: 50%
“…Racial and ethnic discrimination has also been seen as affecting physical health through negative health behaviors, because several studies have consistently shown the relationship between perceived racial/ethnic discrimination and risky behaviors such as smoking and substance abuse (e.g., Borrell et al, 2010;Harris et al, 2006;Landrine & Klonoff, 1996).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…and their negative sequelae (i.e., emotional distress), based on conceptualizations of stigma as a stressor (see Miller & Kaiser, 2001). The link between emotional distress and stigmatizing events, as well as support for the hypothesis that discriminating events cause distress, has been documented in empirical studies on gender and race/ethnicity based stigma (Landrine, Klonoff, Gibbs, Manning, Lund, 1995;Landrine & Klonoff, 1996;Swim, 2001). Several empirical studies among PLH have documented the association between HIV-stigma and depression (Lee, Kochman, Sikkema, 2002;Lichtenstein, Laska, & Claire, 2002;Crandall & Coleman, 2002;Laryea & Gien, 1993;Berger, Ferrans, & Lashley, 2001), as well as anxiety, alienation, social conflict, and poor social support (Berger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%